2015
DOI: 10.1007/s00221-015-4474-7
|View full text |Cite
|
Sign up to set email alerts
|

Eye and hand movement strategies in older adults during a complex reaching task

Abstract: The kinematics of upper limb movements and the coordination of eye and hand movements are affected by aging. These age differences are exacerbated when task difficulty is increased, but the exact nature of these differences remains to be established.We examined the performance of 12 older adults (mean age = 74) and 11 younger adults (mean age = 20) on a multi-phase prehension task. Participants had to reach for a target ball with their preferred hand, pick it up and place it in a tray, then reach for a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Impartments in eye–hand coordination start to appear with advancing age [26,47,48,49]. In our study, a decrease in the aiming index and deterioration in tremor task parameters occurred with increasing age.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Impartments in eye–hand coordination start to appear with advancing age [26,47,48,49]. In our study, a decrease in the aiming index and deterioration in tremor task parameters occurred with increasing age.…”
Section: Discussionsupporting
confidence: 52%
“…Co-ordination of eye and hand movements is affected by ageing. Coast et al [26] observed that older adults move more slowly than younger adults during a complex reaching task, reaching lower peak velocities and taking longer to complete the movement. Additionally, increased complexity of motor tasks is known to enhance difficulties for older adults in controlling manual movements [27].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the kinematics of upper limb movements and the coordination of eye and hand movements are affected by aging, forcing older adults to use a task-dependent eye movement strategy [11]. The subtle changes that occur with age thus appear to reflect a strategy that develops to compensate for deterioration in other systems, such as visual and proprioceptive activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore eye-hand coordination (also known as eye-hand coupling, visuo-manual coordination or oculo-manual synergy) physiology is defined as the coordinated control of eye movements associated with the fine movements of the hands toward a given target, reaching the target and performing the desired work (32). Good directed movements of the upper limb is provided by a large number of neural mechanisms: detection of the target in a three dimensional space (by visual perception), space assessment of the body and of the upper limbs, evaluation of the muscle tone (by proprioception) and execution on-line guidance of the hand trajectory (33)(34)(35). In fact, the essence of eye-hand coordination is the result of the very detailed coupling in space and time of kinetic learning mechanisms.…”
Section: Human-robotic Interface -Role In Stroke Rehabilitationmentioning
confidence: 99%